Business and administrative communication - Locker, Kitty O. (Boston, Mass. : Irwin/McGraw-Hill, 1997)
The building blocks of effective messages. Letters and memos. Interpersonal communication. Reports. Job hunting. Appendices.
Keywords: Business communication; Communication management; Communication in management; Business communication